(untitled) (GYMNASIUM, 2017)
This paper represents an experimental study performed from March 2012 to August 2013, on a group of 50 students from “Hemeiusi” High school, in Bacau County. Students from the experimental group practised one hour of organized physical recreation activities in their leisure time on a weekly basis. The study highlights the efficiency of practising physical leisure exercises by high school rural students. For performing the experiment, we chose physical development assessment standards (height, weight, bust and nutrition indices) (Quetelet = W/H2), physical condition assessment standards (Ruffier test) and events for assessing the level of development of the psychomotor skills (50 m dash in crouching position, 800 m endurance running for girls, 1000 m for boys, oina ball distance throwing from a fixed position, push-ups, body lift from a back lying position, body extension from a stomach lying position). The results show the fact that the values of the physical development indices (height, weight, bust height, nutrition index (Quetelet), physical condition (Ruffier test) and psychomotor development indices are considerably higher at the experimental group than those recorded by the control group, therefore confirming the positive influence of physical leisure exercises on the students’ development.